A Modified Least Significant Bit Replacement: Steganography Method for Handling Random Noise Effect - Usman, Mohammed; Yusuf, Badamasi (IPS Journal of Physical Sciences, 2022)
Steganography is one of the security measures employed at file level to cover information in a carrier. The goal of steganography is to send a confidential message over a network in a way that intruders will not notice it. In steganography, the message is wrapped in an innocent carrier such as image, audio or video file. There are always bits tempering in the process and this changes the looks and appearance of the carrier. The more secret message is embedded in any cover file, the more random noise occurs. Secret message bits when embedded drastically modify the Red Green and Blue (RGB) components’ bits of the carrier, hence, the statistical properties and physical appearance of the carrier change and this draws the attention of intruders to suspect that confidential data is hidden there. This research introduced an improved method of least significant bit replacement to cover secret data using 24 bits bitmap image to handle random noise efficiently so that the Human Visual System (HVS) of intruders will not notice the secret communication. The research reviewed some previous related researches that aimed to reduce the effect of random noise and research gap is identified. The research implemented the new Modified Least Significant Bit Replacement (M-LSBR) method to fill the identified research gap. Five (5) experiments were conducted with 5 (five) varying dimension RGB images and the result gathered that the PSNR value, image quality and message capacity of the new method is better than those achieved by the previous methods, hence, the research gap is filled. Finally, conclusion was drawn and recommendation for future research was suggested.